Homozygous human C3 deficiency. The role of C3 in antibody production, C-1s-induced vasopermeability, and cobra venom-induced passive hemolysis. - Alper, C A (1976)
Studies of the family of a patient with marked deficiency of the third component of complement (C3) demonstrated that the patient was homozygous for a blank allele at the C3 locus, C3-. Metabolic studies with purified radiolabeled C3 in the patient revealed a mildly elevated fractional catabolic rate and a markedly reduced synthesis rate, consistent with a lack of C3 synthesis as the patient's primary defect. There was also a mild increase in the rate of conversion of purified C3 added to her serum and incubated at 37 degrees C in vitro. Major blood group-compatible erythrocytes from a patient with paroxysmal nocturnal hemoglobinuria had the same shortened survival in the C3-deficient patient as in a normal control. Although no leukocytosis developed in the patient in spontaneous infection by pyogenic organisms, there was a normal leukocytosis in response to the injection of thyphoid vaccine. The intradermal injection of C-1s, which produces a marked increase in vasopermeability in the skin of normal subjects, produced no definite change in the patient, possibly implicating C3 or a protein in the alternative pathway as the normal mediator of this response. The patient's serum exhibited near-normal immune adherence activity, confirming the lack of requirement of C3 for this function. C5 inactivation and passive hemolysis of unsensitized guinea pig erythrocytes occurred normally in C3-deficient serum on incubation with cobra venom factor, indicating that C3 is not required for these reactions. The patient's humoral antibody response to both protein and carbohydrate antigens was entirely normal, making it unlikely that C3 is required for antigen processing.